2022
DOI: 10.1002/prep.202200186
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Nitrocellulose by Homogeneous Esterification of Cellulose Based on Ionic Liquids

Abstract: The industrial nitrification system of preparing nitrocellulose (NC) adopts nitric and sulfuric mixed acid, which generates a large amount of waste acid and by‐products, and requires a laborious procedure for the stability treatment. In this study, a novel method was developed for the preparation of NC. NC with a nitrogen content of 12.62 % was prepared in 15 min by homogeneous esterification of cellulose based on [Bmim]Cl (1‐butyl‐3‐methylimidazolium chloride). The samples were characterized by FT‐IR, XRD, Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
4
6
0
Order By: Relevance
“…The DTA curves of the cellulose samples ( Figure 3 c) showed that the decomposition endothermic peak corresponds to a temperature range from 357 °C to 371 °C, with a weight loss of the samples up to 88.6–90.7%, confirming their purity. These results are consistent with the findings of a study on cellulose derived from bitter bamboo stems [ 87 ], which showed the superior thermal stability of cellulose from Giant Miscanthus .…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The DTA curves of the cellulose samples ( Figure 3 c) showed that the decomposition endothermic peak corresponds to a temperature range from 357 °C to 371 °C, with a weight loss of the samples up to 88.6–90.7%, confirming their purity. These results are consistent with the findings of a study on cellulose derived from bitter bamboo stems [ 87 ], which showed the superior thermal stability of cellulose from Giant Miscanthus .…”
Section: Resultssupporting
confidence: 92%
“…The above findings indicate that the obtained CN samples are chemically pure, high-energy biopolymers. Comparing the obtained TGA/DTA data for the CN synthesized from Giant Miscanthus cellulose with those for the CNs derived from cotton [ 87 , 88 ], giant reed [ 9 , 19 ], brown algae [ 22 ], and bitter bamboo stems [ 21 ], indicates their close correspondence. Furthermore, it is demonstrated that all CN samples exhibit high specific decomposition heats ranging from 6.53–8.28 kJ/g.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The characteristic absorption peak at 826 cm À 1 , 747 cm À 1 and 676 cm À 1 can be attributed to the scissor vibration, asymmetric deformation, and symmetrical deformation of the -O-NO 2 [39,40]. The stretching vibration peak of the -CH bonds appeared at about 2909 cm À 1 for NC [40,41]. The weak characteristic absorption peak at about 3581 cm À 1 was attributed to the stretching vibration of the linked À OH in the NC [40],…”
Section: Structural Analyses and Morphologymentioning
confidence: 96%
“…Cellulose nitrates (CNs) are known as a universal, commonly used, inflammable, hydrophobic, and plastic polymer [1] with numerous applications such as the fabrication of membranes [2], biosensors [3], paints and lacquers, filters, plastics, rocket propellants, propellants, and energetic materials [1,[4][5][6][7]. The global market of CNs was estimated to be worth USD 0.86 billion in 2021 and is expected to arrive at USD 1.39 billion by 2030 [6].…”
Section: Introductionmentioning
confidence: 99%